An operational adaptation program of weather modification for the Colorado River Basin - Chappell, Charles F., author; Crow, Loren W., author; Mielke, Paul W., Jr., author; Rasmussen, James L., author; Shobe, William E., author; Stockwell, Homer, author; Wykstra, Ronald A., author; Department of Atmospheric Science, Colorado State University, publisher; Grant, Lewis O., editor (Colorado State University. Libraries, 1969)
Interim report for the period July 1968-June 1969.
Weather modification - an operational adaptation program for the Colorado River Basin
October 1969.
Lewis O. Grant, editor.
Keywords: Weather control -- Colorado River Watershed (Colo.-Mexico)